Author guidelines in dermatological journals discourage the use of the CAse REport guidelines. (23rd September 2015) - Miguel, D.; Elsner, P.
Abstract : Linked Comment: Garcia‐Doval, Br J Dermatol 2015; 173: 894–895 .